Characteristics and times of the care process in a Hospital Level III - Díaz-Chiclayo, Astrid (2020)
Objetive: To describe the characteristics and timing of the process of care for patients treated at the outpatient area during 2014 in the Hospital Base Almanzor Aguinaga Asenjo. Material and Methods: A cross-sectional study was conducted with a sample of 379 new patients in outpatient services. The web application System of Referral and Counter-referrals and the Hospital Management System were used to obtain the sample and data. Results: The actual reference time and effective referral time had a median of 36 days and 39 calendar days respectively; the time of diagnosis had a median of 0 days, the actual treatment time and the effective treatment time had a median of 0 days, the real laboratory time and the effective laboratory time, with medians of 45 and 48 days; and finally, radiological waiting time has a median of 73 days and the waiting time for radiological outcome has a median 0 days. Conclusions: Longer waiting times were the reference time and times for diagnostic aid; which should be especially analyzed to identify the main factors influencing them and improve our health care system.